The Prevalence of Sensitive Skin - Farage, Miranda A. (Frontiers in Medicine, 2019)
Sensitive skin has been described as unpleasant sensory responses to stimuli that should not provoke such sensations. Objectively measurable signs of irritation are not always present in individuals with sensitive skin, however, subjective sensory effects such as, itching, burning, stinging, tightness and dryness, are consistently present. Given the subjective nature of the phenomenon known as sensitive skin, surveys have been a popular approach to evaluating the prevalence of this condition among the general population, and a number of them have been conducted worldwide. Overall, approximately 60-70% of women and 50-60% of men report having some degree of sensitive skin. However, there are differences between populations in various geographies, and perceptions of sensitive skin at specific anatomic sites. This article is a review of survey data on the prevalence of self-declared sensitive skin in various geographies, among different gender and age groups, and at various anatomic sites. In addition, we review the factors that may contribute to sensitive skin, and the physiological characteristics associated with this condition, including impaired barrier function and heightened neural reactions.